KESEHATAN MENTAL DALAM PERSPEKTIF AL-QURAN - Dede Nurwahidah; Masripah, Masripah; Rismayanti, Santi (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2024)
Abstract. Mental health is an important aspect of human life that affects emotional, psychological and social well-being. In recent years, the number of mental health disorders has increased globally, including in Indonesia. This phenomenon emphasizes the need for a more holistic approach in dealing with mental health problems. In a predominantly Muslim society, the Qur'an offers principles that can be used as a solution in maintaining mental health. This study aims to examine the concept of mental health in the Qur'anic perspective and the principles that can be applied in everyday life. Using a qualitative method based on literature study, this research identifies various Qur'anic verses related to mental health. The results showed that the Qur'an provides guidance in managing stress, anxiety, and uncertainty in life through the concepts of faith, tawakal, patience, gratitude, and dhikr. This study confirms that a Qur'an-based spiritual approach can be an alternative in maintaining mental health holistically, especially in facing the challenges of modern life. Keywords: Mental health, Qur'an, spirituality.